'Forbidden Dance': A film treatment by Tonino Guerra. Issue 1 (2nd January 2023) - Hough-Dugdale, Amy
Amidst a suffocating drought, a young, cloistered nun, Angela, experiences desires that draw her out of her convent to adventures, including a tarantella and collective sexual experience of dubious consent, that unsettle her and seem to reorient her relationship to Christ, direct her attention to the Madonna and ask the latter to end the drought in a prayer that is apparently answered.